Baseline comorbidity of cardiovascular-kidney-metabolic syndrome increases the risk of adverse clinical outcomes in patients with chronic kidney disease - Meng, Jiali; Li, Wen; Fu, Wenjing; Zhang, Aihua (Frontiers in Endocrinology, 2025)
IntroductionOur study aims to analyze the relationship between different stage of Cardiovascular-Kidney-Metabolic (CKM) Syndrome in Chronic Kidney Disease (CKD) patients and the risk of progression to all-caused mortality or end-stage renal disease (ESRD).Methods and resultsA retrospective cohort study was performed by collecting baseline data of CKD patients. All participants were followed throughout the course of the study. Cox proportional hazards analysis and Fine-Gray subdistribution model was performed to analyze the prognostic value of different CKM stages on the risk of adverse clinical outcomes (all-caused mortality or progression to ESRD) of these patients. 1,358 patients finally completed the follow-up. Among them, 1,233 patients were alive, and 125 patients had died; and 163 patients progressed to ESRD. Baseline CKM stage 3 (OR=3.906, 95% CI=0.988-16.320, p=0.048) and stage 4 (OR=5.728, 95% CI=1.329-24.698, p=0.019) remain independent risk factors for all-cause mortality in CKD patients, while CKM stage 2b (OR=2.739, 95% CI=1.157-6.486, p=0.022) were identified as having an independent risk factor for progression to ESRD in CKD patients by adjusting confounding factors.ConclusionOur research demonstrated that a high-risk CKM stage can predict adverse clinical outcomes in CKD patients, including all-cause mortality and progression to ESRD.